A flow-through strategy using supported ionic liquids for L-asparaginase purification - Nunes, João C.F.; Almeida, Mafalda R.; de Paiva, Gabriela B. [UNESP]; Pedrolli, Danielle B. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; Neves, Márcia C.; Freire, Mara G.; Tavares, Ana P.M. (Elsevier, 2023)
L-asparaginase (ASNase) is an amidohydrolase enzyme widely distributed in nature, e.g., microorganisms, plants and tissues of several animals. Nevertheless, microorganisms are the preferential source of ASNase since they usually grow in simple substrates and culture conditions. However, a high level of enzyme purity is required by the pharmaceutical industry, in which the applied downstream process may account for up to 80% of the total ASNase production costs. Silica-based supported ionic liquid-like phase (SSILLP) materials are here proposed as alternative immobilization/capture or processing supports for the ASNase purification. SSILLP materials with different alkyl chain lengths at the cation source and Cl− as the counterion were investigated to purify ASNase by the flow-through like mode. Silica functionalized with dimethylbutylpropylammonium chloride ([Si][N3114]Cl) was selected as the most promising material since it displayed the highest purification factor (1.65) and specific activity of ASNase (0.026 U mg−1) achieved. The ASNase purification operating conditions were then optimized through Response Surface Methodology, using pH (range in which enzyme is active) and solid/liquid ratio (S/L ratio) as factors, achieving a maximum purification factor of 3.36. Semi-continuous purification of ASNase was finally performed under the optimized purification conditions (pH 3 and S/L ratio of 15), enabling a purification factor of 5.15. This corresponds to a 3.12- and a 1.53-fold increase in the purification factor obtained compared with the initial screening and batch assays under optimized purification conditions. These findings demonstrate that SSILLP materials can act as simple semi-continuous ASNase purification supports with potential in flow-through downstream processing.
Keywords: Flow-through downstream processing; L-asparaginase; Semi-continuous purification; Silica-based supported ionic liquid-like phase materials